In-situ shear-strain profile assessment in geotechnical array with ground motion data. Issue 165 (February 2023) - Wang, Hai-Yun; Jiang, Wei-Ping
Abstract: In-situ shear-strain profile can be used to evaluate soil dynamic behavior with depth, but also safety of buried lifeline and structures due to seismic wave propagation in soil during an earthquake. Using 199 sets of ground-motion data recorded by six geotechnical arrays with 3–7 sensors in 43 earthquakes, the seismic interferometry by deconvolution method is employed to extract shear-wave velocity profile ( V s, sw ) of seismic wave in each array; ratio of peak particle velocity (PPV) and V s, sw between two successive sensors, PPV/ V s, sw, is computed in each array and assumed to be proxy of the in-situ shear strain. The characteristics of in-situ shear strain profiles in the arrays are studied under seismic loadings in various earthquakes. The relationships of evaluating both the in-situ shear strain profile and the largest in-situ shear strains of the upper soil near the surface are derived from the regression analysis for D and E class sites, respectively. Based on the linear and volumetric threshold shear strains and PGAs and PGVs, the variations of soil behaviors (i.e., linear elastic, nonlinear and plastic behaviors) with the increase of the shear strain or PGA or PGV are studied in the shear strain profiles. The results are as follows. (1) With the increase of PGA and/or PGV in various earthquakes, the in-situ shear strain profiles move towards the larger shear strains and the soil behavior will change to a higher stage or a higher level in the same stage. (2) In the shear strain profile, with the increase of depth, the in-situ shear strains decrease gradually and the soil behavior will change to a lower stage or a lower level in the same stage. (3) Among the shear strain profiles, upper soil has the largest shear strain ( γ max ) and the shallower the soil depth, the larger the shear strain. The relationships between the γ max and PGV and between the γ max and PGA and PGV combination can be used to evaluate the dynamic behavior of upper soil with less than 30 m at a strong motion array or station for D and E class sites. (4) The in-situ shear strains are highly correlated with the PPV and average shear wave velocity measured by the drilling-hole methods ( V s, dh ) combination and with the PPV and V s, dh and center depth between two successive sensors ( H cd ) combination, and increase with the increase of the PPV and decrease with the increase of the V s, dh and/or H cd, respectively. The relationships are recommended to evaluate the in-situ shear strain profile with very high accuracy in the geotechnical array with more than two sensors for D and E class sites. Highlights: The characteristics of in-situ shear strain profiles in the geotechnical arrays are studied under various seismic loadings. Relationships of evaluating the in-situ shear strain profile with very high accuracy are derived for D and E class sites. The variations of soil behaviors with the increase of shear strain or PGA or PGV are studied in the shear strain profiles.